Pelatihan Peningkatan Kompetensi Programming Berbasis Desktop Menggunakan Software Visual Studio Net Pada SMK Swasta Islam Proyek UISU Siantar - Abdi Rahim Damanik; Zulia Almaida Siregar; Susiani Susiani; Indra Gunawan (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Technology in this era is growing rapidly, especially in the field of computers and technology. Where we can see that these developments can facilitate the work of humans or employees and employees. In the education sector, computer science is needed so that teachers can easily provide up-to-date material and are not left behind in today's very rapid technological developments. For this reason, training on programming-based computer science is needed. Many teachers or employees in their understanding of knowing computers are only limited to Ms. Because of that, Office is often used in daily activities. In computer science, there are actually many applications/programs that can make work easier. For this reason, this training was created to introduce one of the application programs in computer science, namely the Visual Studio Net application and the PHPMyAdmin Database. In the training activities carried out at the UISU Siantar Project Islamic Private Vocational School to build a desktop-based information system development process or an application embedded in a computer. Application designed with offline software that has been prepared by the school